Budaya Money Politic di Indonesia dalam Tinjauan Qawa'id Fiqhiyyah - Masdar (UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Indonesia, which adheres to a democratic system, holds the people’s party in the implementation of general elections (elections) which are held every five years. Each edition of the general election (election) is always characterized by the practice of “money politics”. In the development of the term money politics, the media called it “political dowry”. Political dowry is the cost incurred to cover the cost of running a political party (political party) from the grassroots to the central level. Money politics held by successful teams is considered something realistic in getting votes. The general election (election) was initially real, moving towards transactional. This cannot be separated from the behavior of the Indonesian people which continues to develop in responding to the implementation of general elections from the beginning to the end of 2019. This paper responds slightly to the practice of political dowry which continues to exist in every five-year edition. In fact, this practice can be said to have been deeply rooted and become a culture of society in gaining votes in general elections (elections). Fiqh rules are one of the tools in determining cases in Islamic law. Al-’ādatu muhakkamah is one of the five principles of fiqh. al-’ādatu muhakkamah in its concept strongly adheres to two elements, firstly the element of al-’adah (customs) that exists in society, and secondly the element of ‘urf which contains good values in society. Equipped with several branches of the rules, then the writer calls it “al-’ādatu muhakkamah frame”. Because conceptually in these rules there are several limitations that become rules that are not free in absorbing and judging from the cultures or customs that develop in society. Political dowry in Indonesia has become entrenched because this practice has been carried out for quite a long time. based on the concept of al-’adatu muhakkamah cannot be allowed meaning it is prohibited (haram). With the indication that the culture of dowry politics is not part of a culture that has ma’ruf (kindness) values even though this has been assessed by the majority of society as something normal and commonplace. Furthermore, the effect of the political dowry is the beginning (root) of the corrupt practices by the elected candidates in the future.